Penjadwalan Roster Kuliah Menggunakan Metode Welch-Powel - Zulfa, Ira; Septima, Richasanty; Syaputra, Hendri; Eliyin, E; Salim, S (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
Optimal lecture scheduling is an important challenge in higher education institutions, including the Faculty of Engineering, Gajah Putih University. Manually done scheduling often leads to schedule clashes that hinder learning effectiveness. This study aims to overcome this problem by implementing the Welch-Powel graph coloring method in the scheduling system. This method sorts courses by priority and provides coloring to avoid schedule clashes. A literature study was conducted to identify the problem, followed by data collection using questionnaires and interviews. The data obtained is processed in the form of a matrix and represented as a graph. Implementation is carried out in the form of software that is tested to ensure its accuracy and effectiveness. The results show that the Welch-Powel method is effective in producing an optimal lecture schedule and reducing conflicts. The conclusion of this study suggests the use of graph-based scheduling systems to improve scheduling efficiency in the faculty